PERAN IKLIM KERJA DAN KEPEMIMPINAN MEMODERASI PENGARUH KEPUASAN KERJA TERHADAP KINERJA GURU (Students' Journal of Economic and Management, 2012)
This research aims to analyze the role of the Working Climate and Headmaster Leadership Moderating Effect of Job Satisfaction of Performance state junior high school Teachers of Kajen district of Pekalongan Regency. In this research population of 107 people, while the sample was taken as many as 92 people as respondents with a purposive sampling method. Classic asumptiont test making of normality test, heteroskedasticity test, and multikolinearity test.Testing the hypothesis in this study using regression analysis. The results showed the coefficient of determination (Adjusted R Square) of 0.447, meaning that Working Climate, Headmaster Leadership and Job Satisfaction together have 44,7 % influences of state junior high school Teahcers Performance. Test the normality show the normal residual distribution and free from the heteroskedasticity, but at test multikolinearity  happened by the multikolinearity of at variable of moderate working climate and moderate of headmaster leadership. Based on the results of the research can be summarized as follows: (i) Job Satisfaction does not have a positive and significant impact of teacher performance., (ii) Working Climate positive and significant impact of teacher performance, (iii) Headmaster leadership did not have a positive and significant impact on teacher performance, (iv) Working Climate is unknown moderating or not memoderate of Job Satisfaction influence for Teacher Performance, (v) Headmaster Leadership is unkwown moderating or not memoderate of Job Satisfaction for Teacher Performance. Keywords: Working Climate, Headmaster Leadership, Job Satisfaction and Teacher  Performance.